(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2018)
Law 14/2007, of July 3, on Biomedical Research established the legal regimen for the use of human biological samples for biomedical research purposes. This regimen was subsequently implemented by Royal Decree 1716/2011, of November 18, which establishes the basic requirements of authorisation and operation of biobanks with biomedical research goals and the treatment of biological samples of human origin and regulates the operation and organisation of the National Biobank Registry for biomedical research. According with this legal regime, consent for donation samples to biobanks can be given in very broad terms as these institutions guarantee the respect to the donors rights through the implementation of particular policies. Biobanks must have two external committees: the Scientific External Committee and the Ethical External Committee (BEEC). The BEEC verifies compliance with the applicable ethical and legal requirements regarding research projects, for which the samples are aimed, the procurement of the donors’ informed consent, the sample storage conditions and the guarantee of confidentiality of the obtained information. The BEEC must advise the BiobankÂ´s Scientific Manager on the appropriateness of the management procedures for samples and associated data and on other ethical and legal aspects of the biobank’s good practices document. Moreover, the committees must confirm whether the donors’ rights regarding the information obtained, used or stored during the research are respected: the right to; know the overall results of the research, access to personal information and the right to the information that is relevant to the donorÂ´s health that could arise during the research.